Developing an initial set of quality indicators for chiropractic care: a scoping review - Robert Vining; Jennifer Smith; Brian Anderson; Zachary Almquist; Danveshka Wong (BMC, 2024)
Abstract Background Quality indicators are standardized, evidence-based measures of health care quality. Currently, there is no basic set of quality indicators for chiropractic care published in peer-reviewed literature. The goal of this research is to develop a preliminary set of quality indicators, measurable with administrative data. Methods We conducted a scoping review searching PubMed/MEDLINE, CINAHL, and Index to Chiropractic Literature databases. Eligible articles were published after 2011, in English, developing/reporting best practices and clinical guidelines specifically developed for, or directly applicable to, chiropractic care. Eligible non-peer-reviewed sources such as quality measures published by the Centers for Medicare and Medicaid Services and the Royal College of Chiropractors quality standards were also included. Following a stepwise eligibility determination process, data abstraction identified specific statements from included sources that can conceivably be measured with administrative data. Once identified, statements were transformed into potential indicators by: 1) Generating a brief title and description; 2) Documenting a source; 3) Developing a metric; and 4) Assigning a Donabedian category (structure, process, outcome). Draft indicators then traversed a 5-step assessment: 1) Describes a narrowly defined structure, process, or outcome; 2) Quantitative data can conceivably be available; 3) Performance is achievable; 4) Metric is relevant; 5) Data are obtainable within reasonable time limits. Indicators meeting all criteria were included in the final set. Results Literature searching revealed 2562 articles. After removing duplicates and conducting eligibility determination, 18 remained. Most were clinical guidelines (n = 10) and best practice recommendations (n = 6), with 1 consensus and 1 clinical standards development study. Data abstraction and transformation produced 204 draft quality indicators. Of those, 57 did not meet 1 or more assessment criteria. After removing duplicates, 70 distinct indicators remained. Most indicators matched the Donabedian category of process (n = 35), with 31 structure and 4 outcome indicators. No sources were identified to support indicator development from patient perspectives. Conclusions This article proposes a preliminary set of 70 quality indicators for chiropractic care, theoretically measurable with administrative data and largely obtained from electronic health records. Future research should assess feasibility, achieve stakeholder consensus, develop additional indicators including those considering patient perspectives, and study relationships with clinical outcomes. Trial registration Open Science Framework, https://osf.io/t7kgm